2018
DOI: 10.26442/terarkh201890723-29
|View full text |Cite
|
Sign up to set email alerts
|

Cepeginterferon alfa-2b in the treatment of chronic myeloproliferative diseases

Abstract: Purpose of the study. A comparative evaluation of the effectiveness of different therapeutic strategies in patients with polycythemia vera (PV) and essential thrombocythemia (ET). Materials and methods. Patients with PV or ET, diagnosed according to the criteria WHO 2016 were included in the study. The primary endpoint - 6 months of therapy (clinical-hematological and molecular responses). The secondary endpoint - 12 months of therapy (clinico-hematologic, molecular, histological responses). Sixty three patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…IFN- α , one of its isoforms, regulates the generation of the hematopoietic system by affecting human megakaryocyte precursors and immature pluripotent hematopoietic progenitor cells without increasing the risk of cellular mutagenesis, which may provide a viable treatment alternative for MPN patients [ 12 ]. The effect of the JAK2V617F mutant on the clinical phenotype of patients with MPN and the effectiveness of IFN- α against it have been confirmed by numerous clinical studies [ 13 ]. Li et al [ 14 ] found that the gene load of JAK2V617F mutation in patients with MPN was closely related to the severity and duration of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…IFN- α , one of its isoforms, regulates the generation of the hematopoietic system by affecting human megakaryocyte precursors and immature pluripotent hematopoietic progenitor cells without increasing the risk of cellular mutagenesis, which may provide a viable treatment alternative for MPN patients [ 12 ]. The effect of the JAK2V617F mutant on the clinical phenotype of patients with MPN and the effectiveness of IFN- α against it have been confirmed by numerous clinical studies [ 13 ]. Li et al [ 14 ] found that the gene load of JAK2V617F mutation in patients with MPN was closely related to the severity and duration of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…Интерферон имеет долгую историю в лечении МПН. Признано, что ряд пациентов с ИП и ЭТ, получавших терапию интерфероном, достигают полного молекулярного ответа [36][37][38]. Сообщалось о корреляции между достижением полного молекулярного ответа и достижением длительной ремиссии МПН [39].…”
Section: îáñóAeäåíèåunclassified